O017 Il-7 in primary sjÖgren syndrome (PSS) is secreted by salivary gland epithelial cells after ifn stimulation and is associated with B-cell activation. (21st February 2018) - Virone, A; Pascaud, J; Riviere, E; Gottenberg, J-E; Le Guern, V; Mariette, X; Nocturne, G
Abstract : Introduction: pSS is characterised by a strong IFN signature, ectopic germinal centres formation and a chronic blood lymphopenia. IL-7 plays a central part in T cells homeostasis and in lymphoid structures organisation. Objectives: To assess the role of IL-7 in pSS pathogenesis. Methods: IL-7 serum level was assessed in 372 pSS patients and 73 paired controls. Primary cultures of salivary gland epithelial cells (SGEC) from patients and controls were stimulated by Poly I:C 30 ng/ml, IFN-α 600 UI/ml, IFN-γ 5 ng/ml and IFN-λ (IL-28) 25 ng/ml for 72 hours. IL-7 secretion was tested in culture supernatant by ELISA. IL-7 expression after 24 hours stimulation was assessed by quantitative RT-PCR. IL-7 and its receptor's expressions were evaluated in RNA-Seq analysis from cells form salivary glands biopsies (SGB) and PBMC. Results: pSS patients had higher serum IL-7 levels than controls: 7.56 ng/ml±8.52 (mean±SD) versus 4.86 ng/ml±5.59; p<0.0001. A positive correlation with B cells activation markers, IFN-induced chemokines and disease activity markers was observed. In multivariate analysis, serum IL-7 level was associated with CXCL13, anti-SSA, RF, κ light-chain and low C4. SGEC stimulation with Poly I:C, IFN-α, -γ and -λ induced IL-7 protein secretion in the supernatant (p=0.002, p=0.004, p=0.007, p=0.004 respectively). A trend for a greater IL-7 production in pSS patients compared to controls was observed. IL-7 expression was confirmed by quantitative RT-PCR. Among cell subsets purified ex vivo from SGB and PBMC, RNA-Seq analysis showed a greater expression of IL-7 by epithelial cells of patients compared to controls (p=0.03). No difference was observed regarding T and B cells either from biopsies or PBMC. IL-7 receptor expression was equivalent between patients and controls. Analysis of T cells exhaustion profile and IL-7 intracellular signalling are on-going. Conclusions: Our data demonstrate that IL-7 is secreted within the target tissue of pSS by SGEC after stimulation by IFNs. This IFN/IL-7 pathway can be involved in the organisation of ectopic germinal centres found in pSS. But more importantly, since Il-7 is one of the major controller of homeostasis of T cells, this IFN/IL-7 pathway could be involved in the persistent lymphopenia which is a hallmark of the disease, either by favouring exhaustion of T cells or by an impaired function of the IL-7 intracellular signalling. Both mechanisms are currently explored and will be presented. Disclosure of interest: None declared